Inflammation Mediated Epileptogenesis as Possible Mechanism Underlying Ischemic Post-stroke Epilepsy - Tröscher, Anna Regina; Gruber, Joachim; Wagner, Judith N.; Böhm, Vincent; Wahl, Anna-Sophia; von Oertzen, Tim J. (Frontiers in Aging Neuroscience, 2021)
Post-stroke Epilepsy (PSE) is one of the most common forms of acquired epilepsy, especially in the elderly population. As people get increasingly older, the number of stroke patients is expected to rise and concomitantly the number of people with PSE. Although many patients are affected by post-ischemic epileptogenesis, not much is known about the underlying pathomechanisms resulting in the development of chronic seizures. A common hypothesis is that persistent neuroinflammation and glial scar formation causes aberrant neuronal firing. Here, we summarize the clinical features of PSE and describe in detail the inflammatory changes after an ischemic stroke as well as the chronic changes reported in epilepsy. Moreover, we discuss alterations and disturbances in blood-brain-barrier leakage, astrogliosis and extracellular matrix changes in both, stroke and epilepsy. In the end, we provide an overview on commonalities of inflammatory reactions and cellular processes in the post-ischemic environment and epileptic brain and discuss how these research questions should be addressed in the future.